2021
DOI: 10.3390/cancers13153813
|View full text |Cite
|
Sign up to set email alerts
|

The Emerging Role of Circulating Tumor DNA in the Management of Breast Cancer

Abstract: With the incidence of breast cancer steadily rising, it is important to explore novel technologies that can allow for earlier detection of disease as well more a personalized and effective treatment approach. The concept of “liquid biopsies” and the data they provide have been increasingly studied in the recent decades. More specifically, circulating tumor DNA (ctDNA) has emerged as a potential biomarker for various cancers, including breast cancer. While methods such as mammography and tissue biopsies are the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 45 publications
(48 reference statements)
0
8
0
Order By: Relevance
“…Several components of the tumor can be analyzed with liquid biopsy samples, such as circulating tumor DNA (ctDNA), circulating tumor cells (CTCs) and tumor-educated platelets (TEPs) and exosomes. While TEPs and exosomes are currently studied primarily as diagnostic tools, ctDNA and CTCs show promising results in assessing response to treatment and predicting resistance in early breast cancer [ 137 , 138 , 139 , 140 , 141 , 142 ].…”
Section: Predictive Biomarkers Under Investigationmentioning
confidence: 99%
“…Several components of the tumor can be analyzed with liquid biopsy samples, such as circulating tumor DNA (ctDNA), circulating tumor cells (CTCs) and tumor-educated platelets (TEPs) and exosomes. While TEPs and exosomes are currently studied primarily as diagnostic tools, ctDNA and CTCs show promising results in assessing response to treatment and predicting resistance in early breast cancer [ 137 , 138 , 139 , 140 , 141 , 142 ].…”
Section: Predictive Biomarkers Under Investigationmentioning
confidence: 99%
“…The major tumor component that is usually extracted for the identification of tumor characteristics is circulating tumor cells (CTCs) ( 71 ). Except for the CTCs, cell-free DNA (cfDNA), ctDNA ( 72 , 73 ), and c-miRNAs among other circulating non-coding RNAs ( 74 ) can be used as LB markers ( 13 ). The advancement of NGS and digital genomic approaches made biomarkers such as c-RNAs, circulating extracellular vesicles, tumor-educated platelets, proteins, etc.…”
Section: Liquid Biopsy In Breast Cancermentioning
confidence: 99%
“…Unfortunately, there is a lack of effective clinical markers to help detect patients' recurrences and metastases in early stage. In recent years, some studies [ 2 4 ] have shown that the detection of ctDNA, long noncoding RNA, and modulated microRNAs in patients' body fluids can be detected by liquid biopsy for the recurrences and metastases of patients in early stage and is a promising prognostic marker. However, these marker detection with these methods are expensive, the detection methods are not standardized, they are still in research stage, and they have not been applied in clinical practice as a method to monitor tumor metastasis.…”
Section: Introductionmentioning
confidence: 99%